A redefinition of "Spitzenkandidaten": The next EU Commission needs a common political mandate - Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2019)
The European Union's (EU) citizens have voted, and now the EU institutions are due to be reorganised for the next political cycle. Most attention is focussed on personnel issues, but the reorganisation of policy priorities and the structure of the EU Commission are equally important. At the end of Jean-Claude Juncker's term as President of the European Commission, the results are mixed: The Commission has become more focussed and internally coherent, but even at the end of the legislative period, many of its legislative proposals were not able to obtain a majority in the European Parliament and/or the Council of the EU. The mission statement of the political Commission has increasingly proven to be incompatible with the control tasks of the EU's highest executive body. The new Commission will operate in an even more difficult political environment and will itself become more party-politically heterogeneous. Its realignment should therefore also be used as an opportunity to interpret the 'Spitzenkandidaten' principle differently and negotiate a joint political programme for the EU between the Parliament, the Council, and the new Commission.
Keywords: 320